Processed airborne radio-echo sounding data from the POLARGAP survey covering the South Pole, and Foundation and Recovery Glaciers, East Antarctica (2015/2016) - VERSION 2 ... - Ferraccioli, Fausto; Forsberg, Rene; Matsuoka, Kenichi; Olesen, Arne; Jordan, Tom; Corr, Hugh; Robinson, Carl; Kohler, Jack; Bodart, Julien (NERC EDS UK Polar Data Centre, 2024)
During the austral summer of 2015/16, a major international collaboration funded by the European Space Agency (ESA) and with in-kind contribution from the British Antarctic Survey, the Technical University of Denmark (DTU), the Norwegian Polar Institute (NPI) and the US National Science Foundation (NSF), acquired ~38,000 line km of aerogeophysical data. The primary objective of the POLARGAP campaign was to carry out an airborne gravity survey covering the southern polar gap of the ESA gravity field mission GOCE, beyond the coverage of the GOCE orbit (south of 83.5degS), however aeromagnetics and ice-penetrating radar data were also opportunistically acquired. This survey covers the South Pole and Recovery Lakes, as well as parts of the Support Force, Foundation and Recovery Glaciers. Our Twin Otter aircraft was equipped with dual-frequency carrier-phase GPS for navigation, radar altimeter for surface mapping, wing-tip magnetometers, an air-sea gravity meter, and a new ice-sounding radar system (PASIN-2). We ... : ** Instrumentation and Processing: Radar data were collected using the new bistatic PASIN-2 radar echo sounding system operating in full polarimetric mode and mounted on the BAS Twin Otter aircraft "VP-FBL" and operating with a centre frequency of 150 MHz and using a 4-microseconds, 13 MHz bandwidth linear chirp (deep sounding). Chirp compression was applied using a Blackman window to minimise sidelobe levels, resulting in a processing gain of 10 dB. The chirp data was processed using a coherent averaging filter (commonly referred to as unfocused Synthetic Aperture Radar (SAR) processing) with Doppler beam sharpening to enhance the signal to clutter ratio of the bed echo and improve visualisation. The received chirp of 4 microseconds, 13 MHz bandwidth data was compressed, filtered, and decimated from the original trace acquisition rate of 156.25 Hz to 2Hz, equivalent to ~30m in along-track spacing. The chirp data is best suited to assess the bed and internals in deep ice conditions. The coherent pulse-data ...